Factors associated with exclusive breastfeeding by maternal HIV status: a population-based survey in Kenya - Mame M. Diakhate; Jennifer A. Unger; Agnes Langat; Benson Singa; John Kinuthia; Janet Itindi; Edward Nyaboe; Grace C. John-Stewart; Christine J. McGrath (BMC, 2024)
Abstract Background Exclusive breastfeeding (EBF) in the first six months remains low globally, despite known benefits of lower morbidity and mortality among breastfed infants. It is important to understand factors associated with breastfeeding to support optimal breastfeeding practices, particularly in settings with a high burden of HIV. Methods We analyzed data from a population-level survey of mother-infant pairs attending 6-week or 9-month immunizations at 141 clinics across Kenya. Primary outcomes included maternal report of (1) EBF at 6-week visit, defined as currently feeding the infant breast milk only, (2) EBF for the first 6-months of life, defined as breastfeeding or feeding the infant breast milk only with no introduction of other liquids or solid foods until 6 months, and (3) continued breastfeeding with complementary feeding at 9-months. Correlates of breastfeeding practices were assessed using generalized Poisson regression models accounting for facility-level clustering. Results Among 1662 mothers at 6-weeks, nearly all self-reported breastfeeding of whom 93% were EBF. Among 1180 mothers at 9-months, 99% had ever breastfed, 94% were currently breastfeeding and 73% reported 6-month EBF. At 6-weeks, younger age (< 25 years) (adjusted Prevalence Ratio (aPR) 0.96; 95% CI 0.93, 0.99), lower education (aPR 0.96; 95% CI 0.93, 0.99) and recent infant illness (aPR 0.97; 95% CI 0.94, 1.00) were associated with lower EBF prevalence while women living with HIV (WLWH) had higher EBF prevalence (aPR 1.06; 95% CI 1.02, 1.10) than women without HIV. 6-month EBF prevalence was 26% higher in WLWH (aPR 1.26; 95% CI 1.15, 1.35) than women without HIV, 14% lower in women reporting mild or above depressive symptoms (aPR 0.86; 95% CI 0.76, 0.99) than those with none or minimal depressive symptoms, and 15% lower in women with versus without history of intimate partner violence (aPR 0.85; 95% CI 0.74, 0.98). At 9-months, WLWH had a lower prevalence of continued breastfeeding with complementary feeding (aPR 0.73; 95% CI 0.64, 0.84) than women without HIV. Conclusion WLWH had higher EBF prevalence in the first 6-months, but lower prevalence of continued breastfeeding at 9-months. Strategies to support EBF and continued breastfeeding beyond 6-months postpartum, particularly among WLWH, are needed.